Interlanguage and Its Implications to Second Language Teaching and Learning - Guo, Qiaolan (Pacific International Journal, 2022)
Interlanguage refers to the knowledge system which is formed in a certain period in learners’ second language learning process. The study on interlanguage is of great significance in the field of second language acquisition. This paper elaborates on the definition and characteristics of interlanguage, and analyzes five main factors contributing to the formation of interlanguage.The first factor is language transfer, especially negative language transfer; the second is transfer of language training, which means teacher overemphasized one form or pattern and used inappropriate or even faulty teaching materials, at the same time, teacher’s incompetence in identifying non-English forms may also lead to interlanguage; the third factor is strategies of second language learning, which is often thought to be culture bound; the fourth factor is strategies of second language communication; the last factor is overgeneralization of target language. Through close study of the factors leading to interlanguage, this paper draws some implications to second language teaching and learning: the first is reducing negative transfer. Teachers can emphasize the importance of reinforcing the learners’ responses by rewarding target-like responses and correcting non-target-like ones, and learners should be encouraged to read as much as possible the English writings by native English writers. Second is increasing cultural information teaching. Teachers can choose some culturally-authentic materials from the native speech community and adopt various cultural teaching techniques. At the same time, to optimize language input environment. Teachers are supposed to equip with high levels of L2 competence and provide students with the right thing in the right way. Another way to reduce language transfer is to increase the opportunity for output. Moreover, we can see that making errors is a part of language and error-correction can help interlanguage develop towards the TL, hence, adopting proper correction strategies are of great importance. Last but not least, applying proper learning strategies is also a better way to avoid the occurrence of interlanguage.